“Estudio de factibilidad para la creación de una pequeña empresa productora de mermeladas de frutas cítricas en el cantón La Maná provincia de Cotopaxi, año 2022”. - Perea Mayorga, Ana Nohemi (2023)
The current research entitled Feasibility study to create a small company producing citrus fruit jam "NAAN" in La Maná canton, Cotopaxi province, the year 2022, was conducted to know the feasibility of the implementation of this small company producing jam. To fulfill the proposed objectives was necessary to conduct research: formative, bibliographic, descriptive, and field research that allowed reaching theoretical and bibliographic information from various authors; likewise, the descriptive and field research was essential to diagnose the supply and demand of jam products through the application of surveys directed to traders and consumers of the canton. Within this project were taken into the direct and indirect beneficiaries, as direct beneficiaries have the owners of the small business, potential consumers, and potential suppliers, and the indirect ones have the Internal Revenue Service (SRI), the Municipal Government of La Maná, and the Fire Department. The market study established that there was a current annual demand of 248,880 and a supply of 280,270, giving an unsatisfied of 320,330 of which was projected to cover with a yearly production of 256,346 citrus fruit jams (orange, tangerine, and lemon) in the presentation of 100gm, The technical study also described the sketch of the location, availability of resources, production process, distribution of infrastructure, project requirements, organization and the legal framework necessary for the operation of the company. The economic and financial study showed that the total investment required was 8,956.50 was financed at 10% through equity and 90% through a bank loan from BanEcuador with an interest rate of 1%. With a general equilibrium point of $0.14, the NPV for the small company producing NAAN jam was $392,429.02, an IRR of 82%, and a cost-benefit ratio of $2.61, values that demonstrated the feasibility of this proposal. Among the most relevant impacts are the environmental and social since this project aims to reduce solid and liquid contamination produced by wasting fruit and offer employment opportunities for Los Lamanenses.